Whisper of the heart [videorecording (DVD)] = Mimi o sumaseba - Kondō, Yoshifumi; Snow, Brittany, 1986-; Thorne-Smith, Courtney; Elwes, Cary, 1962-; Sikking, James, 1934-; Smart, Jean; Gould, Harold, 1923-2010 (Walt Disney Home Entertainment : Distributed by Buena Vista Home Entertainment, 2006)
A schoolgirl named Shizuku, who longs to discover her true talents, meets the mysterious Seiji, a boy who is determined to follow his dreams, and The Baron, a magical cat who helps her listen to the whispers in her heart.